Green Economy: Opportunities and Challenges for the Industrial Sector Amid Climate Change Issues - Loso Judijanto (Nomico, 2025)
This study aims to explore the understanding, challenges, and opportunities faced by the industrial sector in implementing the green economy concept amid climate change issues. Using a qualitative approach, this research investigates the experiences of large industries and MSMEs in transitioning toward a green economy, as well as its impact on production processes and competitiveness. The findings reveal a disparity in understanding between large enterprises and MSMEs, with larger companies generally being more prepared to adopt green technologies. In contrast, MSMEs tend to perceive this transition as a high-cost burden. The study also identifies key driving factors such as government regulations, market demands, and fiscal incentives that can accelerate green economy adoption. However, obstacles such as high investment costs, limited human resources, and policy uncertainty remain significant challenges. These findings highlight the importance of government support and cross-sector collaboration in accelerating a more inclusive transition toward a green economy.